Greater externalizing personality traits predict less error‐related insula and anterior cingulate cortex activity in acutely abstinent cigarette smokers. (13th December 2013) - Carroll, Allison J.; Sutherland, Matthew T.; Salmeron, Betty Jo; Ross, Thomas J.; Stein, Elliot A.
Abstract Attenuated activity in performance‐monitoring brain regions following erroneous actions may contribute to the repetition of maladaptive behaviors such as continued drug use. Externalizing is a broad personality construct characterized by deficient impulse control, vulnerability to addiction and reduced neurobiological indices of error processing. The insula and dorsal anterior cingulate cortex (dACC) are regions critically linked with error processing as well as the perpetuation of cigarette smoking. As such, we examined the interrelations between externalizing tendencies, erroneous task performance, and error‐related insula and dACC activity in overnight‐deprived smokers (n = 24) and non‐smokers (n = 20). Participants completed a self‐report measure assessing externalizing tendencies (Externalizing Spectrum Inventory) and a speeded Flanker task during functional magnetic resonance imaging scanning. We observed that higher externalizing tendencies correlated with the occurrence of more performance errors among smokers but not non‐smokers. Suggesting a neurobiological contribution to such suboptimal performance among smokers, higher externalizing also predicted less recruitment of the right insula and dACC following error commission. Critically, this error‐related activity fully mediated the relationship between externalizing traits and error rates. That is, higher externalizing scores predicted less error‐related right insula and dACC activity and, in turn, less error‐related activity predicted more errors. Relating such regional activity with a clinically relevant construct, less error‐related right insula and dACC responses correlated with higher tobacco craving during abstinence. Given that inadequate error‐related neuronal responses may contribute to continued drug use despite negative consequences, these results suggest that externalizing tendencies and/or compromised error processing among subsets of smokers may be relevant factors for smoking cessation success.